Bloodless tandem autologous transplant in Jehovah's Witness patients. (November 2018) - Khan, Rafiullah; Mott, Sarah; Schultz, Allyson; Jethava, Y.; Tricot, Guido
Abstract Tandem autologous transplants are generally the preferred therapy for newly diagnosed intermediate- and high-risk myeloma patients. More Jehovah's Witnesses (JW) are receiving single autologous peripheral blood stem cell transplants (PBSCTs). However, tandem autologous transplants have not been reported in JW patients. We performed a retrospective study of 54 patients, including four JW patients who received tandem autologous transplants between August 2000 and January 2017 and the last 50 consecutive tandem autologous transplants performed between August 2014 and August 2016. The bleeding complications, number, and cost of transfusions of blood products were compared. The median number of CD34 cells infused in non-JW patients was 8.16 million cells/kg versus 9.44 million cells/kg in JW patients. During the first 30 days, one JW experienced Grade III pulmonary hemorrhage, while none of the non-JW patients had a Grade III or higher bleeding problem. After tandem autologous transplants, complete remission was achieved in 88% of non-JW, compared with 75% in JW patients. In the first 30 days post-transplant, median platelet and packed red blood cell (PRBC) transfusions in non-JW patients was 2 (range: 0–40) and 1 (range: 0–11), respectively. Total cost of PRBC and platelet transfusions for the 50 non-JW was $214, 664 (average $2147/transplant). Tandem autologous transplants can thus be performed safely without a single blood transfusion.